Preferred Sources of Health Information in Persons With Multiple Sclerosis: Degree of Trust and Information Sought - Marrie, Ruth Ann; Salter, Amber R; Tyry, Tuula; Fox, Robert J; Cutter, Gary R (JMIR Publications, 2013)
BackgroundEffective health communication is important for informed decision-making, yet little is known about the range of information sources used by persons with multiple sclerosis (MS), the perceived trust in those information sources, or how this might vary according to patient characteristics. ObjectiveWe aimed to investigate the sources of health information used by persons with MS, their preferences for the source of health information, and levels of trust in those information sources. We also aimed to evaluate how these findings varied according to participant characteristics. MethodsIn 2011, participants in the North American Research Committee on Multiple Sclerosis (NARCOMS) Registry were asked about their sources of health information using selected questions adapted from the 2007 Health Information National Trends (HINTS) survey. ResultsOf 12,974 eligible participants, 66.18% (8586/12,974) completed the questionnaire. Mass media sources, rather than interpersonal information sources, were the first sources used by 83.22% (5953/7153) of participants for general health topics and by 68.31% (5026/7357) of participants for MS concerns. Specifically, the Internet was the first source of health information for general health issues (5332/7267, 73.40%) and MS (4369/7376, 59.23%). In a logistic regression model, younger age, less disability, and higher annual income were independently associated with increased odds of use of mass media rather than interpersonal sources of information first. The most trusted information source was a physician, with 97.94% (8318/8493) reporting that they trusted a physician some or a lot. Information sought included treatment for MS (4470/5663, 78.93%), general information about MS (3378/5405, 62.50%), paying for medical care (1096/4282, 25.59%), where to get medical care (787/4282, 18.38%), and supports for coping with MS (2775/5031, 55.16%). Nearly 40% (2998/7521) of participants had concerns about the quality of the information they gathered. ConclusionsAlthough physicians remain the most trusted source of health information for people with MS, the Internet is the first source of health information for most of them. This has important implications for the dissemination of health information.